ANALISIS PEMANFAATAN LAYANAN TELEMEDICINE PASCA PANDEMI COVID-19 DI JAWA TENGAH - Santoso, Bagus Satrio; Budiyanti, Rani Tiyas; Nandini, Nurhasmadiar (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Utilization of telemedicine services decreased after the pandemic conditions improved. Telemedicine utilization is closely related to the internet network. Central Java is the province with the lowest internet penetration rate in Java. The purpose of this study was to determine the factors related to the utilization of telemedicine services after the COVID-19 pandemic in Central Java. This type of research was quantitative research with a cross-sectional study design. This research was conducted in December 2023-March 2024. The sample in this study was 300 people in Central Java. The sampling technique used accidental sampling method. The analysis used was univariate analysis and bivariate analysis using the Chi Square test. This study showed that 50.3% of respondents utilized telemedicine services after the pandemic. Utilized telemedicine services after the pandemic related to education (p-value <0.001), knowledge (p-value <0.001), trust (p-value <0.001), family support (p-value <0.001), accessibility (p-value <0.001), and need (p-value <0.001). All independent variables in this study (education, knowledge, trust, family support, accessibility, needs) are associated with the utilization of telemedicine services after the COVID-19 pandemic.